Occupational Noise Exposure and Its Impact on Palm Oil Mill Workers’ Health - Wondi, Nurul Hidayah; Ismail, Siti Norziah; Ruslan, Rumaizah (Research in Management of Technology and Business, 2020)
Palm oil mills are one of the noisiest industrial workplaces, whereby extreme noise poses a risk to the health of the workers and can cause severe consequences. Occupational noise exposure gradually affects auditory and non-auditory aspects of health. The set of symptoms are referred to as having fatigue, head injuries, tinnitus, trauma disease, and high blood pressure. Therefore, the objectives of this study are to determine the occupational noise exposure level among the Palm Oil Mill workers, to evaluate the occupational noise exposure level based on a prospective study among Palm Oil Mill workers, and to identify the impact of occupational noise exposure on Palm Oil mill workers’ health. The study was assessed based on questionnaires, environmental noise exposure level (SLM), and personal observation. The participants were 80 workers from different selected work stations. It is reported that the effect of workplace noise exposure shows the highest noise level at Station 2 (Kernel, Press, Sterilizer station, Oil room) ranges from 90.3 dB(A) to 101.2 dB(A) while Station 1 (Ramp Station) shown the lowest noise level 82.2 to 98.1 dB(A). In addition, the quantitative results have shown that occupational noise exposure had a positive impact on worker’s health. Therefore, it is highly recommended to raise awareness of workers ’ health and improve control of palm oil noise exposure. Generally, palm oil milling employees are exposed to high noise levels. This research briefs the outcomes and impacts of occupational noise exposure faced by the workers during the working hours and the rest of the working hours.